Anti-Fungal Efficacy and Mechanisms of Flavonoids - Mohammed Saleh Al Aboody; Suresh Mickymaray (MDPI AG, 2020)
The prevalence of fungal infections is growing at an alarming pace and the pathogenesis is still not clearly understood. Recurrence of these fungal diseases is often due to their evolutionary avoidance of antifungal resistance. The development of suitable novel antimicrobial agents for fungal diseases continues to be a major problem in the current clinical field. Hence, it is urgently necessary to develop surrogate agents that are more effective than conventional available drugs. Among the remarkable innovations from earlier investigations on natural-drugs, flavonoids are a group of plant-derived substances capable of promoting many valuable effects on humans. The identification of flavonoids with possible antifungal effects at small concentrations or in synergistic combinations could help to overcome this problem. A combination of flavonoids with available drugs is an excellent approach to reduce the side effects and toxicity. This review focuses on various naturally occurring flavonoids and their antifungal activities, modes of action, and synergetic use in combination with conventional drugs.